Caribbean integration and global Europe : implications of the EPA for the CSME - Girvan, Norman ([s.n.] [S.l.], 2008)
Assesses the compatibility of the CARIFORUM-EC EPA with the proposed CARICOM Single Market and Economy. Concludes that the CSME will be superseded by the EPA, which involves a high degree of bilateral integration of individual CARIFORUM countries with Europe in trade, investment and regulatory policies. Provides pointers on how the EPA could be modified to resolve this dilemma and to increase its effectiveness as an instrument of development and regional integration.